“Do I Look Fat in This?”: The Role of the Mother-Daughter Relationships in Determining Body Image - Eboni Baugh (EDIS, 2007)
FCS8838, a 3-page fact sheet by Eboni Baugh, explores the importance of the mother-daughter relationship to girls developing their body images. Learn how mothers can play a crucial role in ensuring that girls have a healthy self-image and do not engage in destructive dieting or eating patterns. Published by the UF Department of Family, Youth and Community Sciences, April 2007.